Molecular phylogeography of Troglophilus cave crickets (Orthoptera, Rhaphidophoridae): A combination of vicariance and dispersal drove diversification in the East Mediterranean region. (15th June 2017) - Allegrucci, Giuliana; Ketmaier, Valerio; Di Russo, Claudio; Rampini, Mauro; Sbordoni, Valerio; Cobolli, Marina
Abstract: In this study, we investigated the molecular phylogenetic divergence and historical biogeography of cave crickets belonging to the genus Troglophilus (Orthoptera, Rhaphidophoridae) from caves in eastern Mediterranean and Anatolia regions. Three mitochondrial DNA genes ( COI, 12S rDNA, and 16S rDNA ) and two nuclear ones ( 18S rDNA and 28S rDNA ) were amplified and partially sequenced to reconstruct phylogenetic relationships among most of the known Troglophilus species. Results showed a well‐resolved phylogeny with three main clades representing the Balkan, the Anatolian, and the Cycladian–Cretan lineages. Based on Bayesian analyses, we applied a relaxed molecular clock model to estimate the divergence times between these three lineages. Dating estimates indicate that radiation of the ingroup might have been triggered by the opening of the Mid‐Aegean trench, while the uplift of the Anatolian Plateau in Turkey and the changes of relief, emergence, and disappearance of orographic and hydrographical barriers in the Balkan Peninsula are potential paleogeographic events responsible for the initial diversification of the genus Troglophilus . A possible biogeographic scenario, reconstructed using S‐DIVA with RASP software, suggested that the current distribution of Troglophilus species can be explained by a combination of both dispersal and vicariance events that occurred in particular in the ancestral populations. The radiation of Troglophilus species likely started from the Aegean and proceeded eastward to Anatolia and westward to the Balkan region. Results are additionally compared to those available for Dolichopoda, the only other representative genus of Rhaphidophoridae present in the Mediterranean area. Abstract : We reconstructed the molecular phylogeny and historical biogeography of cave crickets belonging to the genus Troglophilus from caves in eastern Mediterranean, using both mitochondrial and nuclear genes. The well‐resolved phylogeny showed three main clades representing the Balkan, the Anatolian, and the Cycladian–Cretan lineages. Both dispersal and vicariance events, occurred especially in the ancestral populations, can explain the current distribution of Troglophilus species whose radiation likely started from the Aegean and proceeded eastward to Anatolia and westward to the Balkan region.